Biochar – a sustainable soil conditioner for improving soil health, crop production and environment under changing climate: a review - Pandian, Kannan; Vijayakumar, Shanmugam; Mustaffa, Mohamed Roshan Abu Firnass; Subramanian, Ponmani; Chitraputhirapillai, Swaminathan (Frontiers in Soil Science, 2024)
Land degradation and climate change, two intricately intertwined phenomena, demand appropriate management solutions to effectively tackle the escalating issues of food and nutritional security. In this context, the realm of agriculture confronts formidable challenges in its pursuit of soil resource reclamation, improving water quality, mitigating climate change, and maintaining soil and natural resources for posterity. Central to these aspirations is the preservation of an optimum organic matter, serving as a linchpin threshold is crucial for protecting the physical, chemical, and biological integrity of the soil, while simultaneously sustaining agricultural productivity. To address these multifaceted challenges, the introduction of diverse organic amendments has emerged as a crucial strategy.Noteworthy among these is the application of biochar, which functions as a soil conditioner capable of bolstering soil health, mitigating the impact of climate change, and securing global food security. Biochar is a carbon-enriched substance produced through pyrolysis of assorted biomass waste. It has a larger surface area, higher cation exchange capacity, and an extended carbon storage capability. The strategic integration of biochar production and subsequent soil application engenders an array of benefits, encompassing the amelioration of soil physical properties, augmented retention and the availability of nutrients, and the enhancement of biological activity, resulting in higher agricultural yields and societal benefits through the curtailment of soil to atmosphere greenhouse gas emissions. Additionally, biochar demonstrates its efficacy in the realm of environmental restoration by serving as a medium for extraction and elimination of heavy metals, which often pervade aquatic ecosystems and soil matrices. This review addressed the need for biochar production, characterization, soil health, the possibility for environmental restoration, and crop yield fluctuations owing to climate change.